A multicentre comparison between Child Pugh and Albumin‐Bilirubin scores in patients treated with sorafenib for Hepatocellular Carcinoma. (22nd June 2016) - Edeline, Julien; Blanc, Jean‐Frédéric; Johnson, Philip; Campillo‐Gimenez, Boris; Ross, Paul; Ma, Yuk Ting; King, Judy; Hubner, Richard A.; Sumpter, Kate; Darby, Suzanne; Evans, Jeff; Iwuji, Chinenye; et al.
Abstract: Background & Aims: The Albumin‐Bilirubin (ALBI) grade was proposed as an objective means to evaluate liver function in patients with Hepatocellular Carcinoma (HCC). ALBI grade 1 vs 2 were proposed as stratification factors within the Child Pugh (CP) A class. However, the original publication did not provide comparison with the subclassification by points (5–15) within the CP classification. Methods: We retrospectively analysed data from patients treated with sorafenib for HCC from 17 centres in United Kingdom and France. Overall survival (OS) was analysed using the Kaplan– Meier method and a Cox regression model. Discriminatory abilities of the classifications were assessed with the log likelihood ratio, Harrell's C statistics and Akaike information criterion. Results: Data from 1019 patients were collected, of which 905 could be assessed for both scores. 92% of ALBI grade 1 were CP A5 while ALBI 2 included a broad range of CP scores of which 44% were CP A6. Median OS was 10.2, 7.0 and 3.6 months for CP scores A5, A6 and >A6, respectively ( P < 0.001), Hazard Ratio (HR) = 1.60 (95%CI: 1.35–1.89, P < 0.001) for A6 vs A5. Median OS was 10.9, 6.6 and 3.0 months for ALBI grade 1, 2 and 3, respectively ( P < 0.001), HR = 1.68 (1.43–1.97, P < 0.001) for grade 2 vs 1. Discriminatory abilities of CP and ALBI were similar in the CP A population, but better for CP in the overall population. Conclusions: Our findings support the use CP class A as an inclusion criterion, and ALBI as a stratification factor in trials of systemic therapy.